Donne sikh e diaspora: intrecciare casa, comunicazioni e legami nella Val di Chiana senese - Sikh Women and Diaspora: Weaving Home, Communications, and Bonds in the Sienese Val di Chiana - Francesca Scarselli (EtnoAntropologia, 2025)
This paper explores homemaking practices among Sikh women in rural Tuscany, highlighting how domestic spaces become key sites of diasporic identity, negotiation, and resistance. Through ethnographic narratives, it shows how women reconfigure family hierarchies and gender roles while rooting their presence in marginal territories. Homes and objects emerge as agents of transformation, where care, control, and belonging intersect. The rural diaspora becomes a space of possibility, rearticulated through everyday practices.